Effects of IT capability on Performance of Manufacturing Firms in Nairobi City County Kenya - Gitau, Lucy; Nzuki, David; Musau, Felix (Technium Social Sciences Journal, 2022)
Although manufacturing firms support economic development, wealth creation and poverty alleviation, a dismal performance has been reported. In Kenya, the share of gross domestic product (GDP) from manufacturing sector has remained below 10 per cent while its growth rate remained at about 5 percent in the last 10 years. This has been attributed to low innovation and technology diffusion. This study examined the effects of IT capability on firm performance. The study was anchored on Resource Based View, and Dynamic Capability Theory. Positivism philosophical approach, descriptive and explanatory research design were adopted. Using stratified and random sampling techniques, a sample of 222 manufacturing firms from Nairobi City County, was obtained. A semi-structured questionnaire was prepared and used for data collection. To ascertain reliability, Cronbach’s alpha coefficient measure of 0.875 was obtained. Research experts confirmed validity of the study instrument. The data was analysed through descriptive statistics to condense the survey data. To test hypotheses, inferential statistics was used. The results showed a positive significant effect of IT infrastructure capability (B=0.247, p=0.005 < 0.05), IT personnel capability (B=0.226, p=0.044 < 0.05), IT management capability (B=0.187, p=0.018 < 0.05) and IT reconfiguration capability (B=0.291, p=0.001 < 0.05) on performance. The study findings also exhibited a 49.2 per cent explanatory power of IT capability on firm performance. Study findings provide a framework for improving firm performance. Subsequently, firm managers should create interventions on IT capability to enhance and sustain superior firm performance.